Exploration of the Implementation of Deep Learning Approach in Teaching Mathematics in Secondary Schools - Pujawati, Fitria; Azkia, M. Naufal; Susilawati, Wati (Universitas Negeri Semarang, 2025)
This study explored how mathematics teachers interpret and implement deep learning approaches in classroom instruction and the challenges they encounter. Using a qualitative case study design, data were collected from five teachers through an open-ended online questionnaire and two in-depth interviews. Thematic analysis was conducted following the Miles, Huberman, and Saldaña framework. The findings revealed that teachers view deep learning as a student-centered approach that emphasizes conceptual understanding, critical thinking, and emotional engagement. Teachers employ various strategies such as group discussions, problem-based learning, contextual problem solving, discovery learning, open-ended math projects, game-based assessments, and the CORE model. However, challenges arose in tailoring strategies to meet diverse student needs, managing time constraints, and dealing with limited infrastructure. The study concludes that, although teachers value deep learning, its effective classroom application depends on stronger institutional support and flexible pedagogical models. These findings offer practical insights into how deep learning is interpreted and practiced in Indonesian mathematics classrooms.